Comparative evaluation of efficacy of 0.2% sodium hypochlorite (Hi Wash) mouthwash with 0.2% chlorhexidine mouthwash on plaque-induced gingivitis: A clinical trial - Rohit Mishra; Kabbur Thippanna Chandrashekar; Vandana Dubey Tripathi; Anushree Hazari; Blessy Shin Sabu; Anurag Sahu (Wolters Kluwer Medknow Publications, 2019)
Background: Bleeding gums are one of the common complaints to visit a dentist. Mechanical removal of plaque alone is not sufficient for the reduction of gingival inflammation associated with plaque. Mouthwashes are supplemented to it as a homecare product. The objective of this study is to evaluate the efficacy of 0.2% sodium hypochlorite mouthwash on plaque and gingival inflammation and to assess the clinical parameters of gingivitis patients from baseline to 21 days with the use of 0.2% sodium hypochlorite and 0.2% chlorhexidine mouthwashes. Materials and Methods: This clinical trial study included 60 patients with gingival inflammation evaluated using clinical parameters such as bleeding on probing index, plaque index, and gingival index at baseline and 21 days. Group A patients were given Hi Wash mouthwash and Group B 0.2% chlorhexidine mouthwash with 30 patients in each group. Results: The scores for clinical parameters were significantly reduced after 21 days in Group A and Group B patients, and there was a reduction in plaque-associated gingival inflammation without scaling and root planning. Conclusions: 0.2% sodium hypochlorite mouthwash is as effective as 0.2% chlorhexidine for the treatment of gingivitis as it is an adjunct to mechanical plaque removal in terms of safety, less side effects, less staining and can be used as a routine mouthwash.